2018
DOI: 10.1093/ndt/gfy218
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evidence on haemodiafiltration

Abstract: Haemodiafiltration (HDF) combines diffusive and convective solute removal in a single treatment session. HDF provides a greater removal of higher molecular weight uraemic retention solutes than conventional high-flux haemodialysis (HD). Recently completed randomized clinical trials suggest better patient survival with online HDF. The treatment is mainly used in Europe and Japan. This review gives a brief overview of the presently available evidence of the effects of HDF on clinical end points, it speculates on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 50 publications
4
36
0
2
Order By: Relevance
“…However, also at lower levels of convection volume, HDF has a better control of blood pressure over time, improves intradialytic hemodynamic stability, reduces markers of inflammation, and leads to a better removal rate of β2-microglobulin. 9,20 Nevertheless, the present study shows that LVH may improve in ESRD patients receiving chronic HD and the pooled mean difference between pre-and post-procedural LVMi was −8.0 g/m 2 . This is possibly secondary to the prevention and control of anemia, control of volume overload, use of antihypertensive drugs, prevention and treatment of hyperphosphatemia, and administration of vitamin D. 21 Our study has the usual limitations of meta-analysis of observational studies.…”
Section: Ta B L E 3 Meta-regression For Left Ventricular Mass Index (mentioning
confidence: 47%
See 4 more Smart Citations
“…However, also at lower levels of convection volume, HDF has a better control of blood pressure over time, improves intradialytic hemodynamic stability, reduces markers of inflammation, and leads to a better removal rate of β2-microglobulin. 9,20 Nevertheless, the present study shows that LVH may improve in ESRD patients receiving chronic HD and the pooled mean difference between pre-and post-procedural LVMi was −8.0 g/m 2 . This is possibly secondary to the prevention and control of anemia, control of volume overload, use of antihypertensive drugs, prevention and treatment of hyperphosphatemia, and administration of vitamin D. 21 Our study has the usual limitations of meta-analysis of observational studies.…”
Section: Ta B L E 3 Meta-regression For Left Ventricular Mass Index (mentioning
confidence: 47%
“…A recent individual participant data analysis on the results of the four large randomized controlled trials comparing HD and HDF demonstrated that the risk of all‐cause and cardiovascular mortality was significantly lower in the HDF group. However, a post‐hoc analysis stratifying patients by achieved convection volume showed that a minimum volume of 23L/session was required for HDF to achieve such benefit …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations